In Situ Architecting Endogenous Heterojunction of MoS2 Coupling with Mo2CTx MXenes for Optimized Li+ Storage (Adv. Mater. 5/2022). Issue 5 (3rd February 2022) - Zhu, Shuang; Wang, Changda; Shou, Hongwei; Zhang, Pengjun; Wan, Ping; Guo, Xin; Yu, Zhen; Wang, Wenjie; Chen, Shuangming; Chu, Wangsheng; Song, Li
Abstract : Hetero‐MXenes Endogenous heterojunction of 2D MXenes with unique structure shows inspiring potential in energy applications. In article number 2108809, Li Song and co‐workers successfully synthesize unique endogenous hetero‐MXenes of amorphous MoS2 coupling with fluoride‐free Mo2 CT x directly from Mo2 Ga2 C MAX via an optimal in situ hydrothermal strategy. The distinctive morphology and heterojunction structure endow the hetero‐MXenes with extraordinary structural stability and an optimized Li + ‐storage mechanism, with improved charge transport and Li + ‐adsorption capabilities.